Superior laryngeal nerve transection for neuropathic cough: A pilot study. Issue 5 (October 2020) - Bradley, Joseph P.; Gross, Jennifer; Paniello, Randal C.
Abstract: Objective: To describe a novel surgical therapy for the treatment of medically refractory neuropathic cough, in which carefully selected subjects undergo surgical transection of the internal branch of the superior laryngeal nerve (iSLN). Methods: Subjects with a diagnosis of neuropathic cough, who were not improved after two medication trials, underwent iSLN block with local anesthetic in the office. While anesthetized, they underwent provocative testing to determine whether the nerve block improved their symptoms; if so, a modified barium swallow study (MBSS) was performed to determine whether they still swallowed safely without supraglottic sensation. Those who passed this screening were offered operative iSLN transection. We retrospectively reviewed our results to date. Results: Six subjects (5 females, ages 46–71), with neuropathic cough symptoms for 2–15 years, passed the screening and underwent iSLN transection procedures. At a mean follow-up of 8.2 months, significant symptomatic relief was experienced by 5/6 subjects, with Cough Severity Index (CSI) scores averaging 34.83 ± 6.94 pre-op (range 36–40) and 15.5 ± 11.81 post-op (range 0–29) ( p = 0.043). Operative time averaged 49 min (range 30–64). There were no major complications. No subjects experienced post-op aspiration problems. Conclusion: This preliminary data supports iSLN transection as a viable option for subjects with refractory neuropathic cough. Our screening algorithm identifies subjects that would be expected to improve with this procedure and confirms a safe swallow.